2022
DOI: 10.1272/jnms.jnms.2022_89-205
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon Response to Glucose Challenge in Patients with Idiopathic Postprandial Syndrome

Abstract: Background: Postprandial syndrome is characterized by hunger, weakness and anxiety neurosis occurring after meals. Although abnormal glucagon response has been suggested, inaccuracies of the conventional glucagon measurement method have prevented from precise analysis. Recently, a more reliable dual-antibody sandwich enzyme-linked immunosorbent assay for glucagon has been developed. Methods:We conducted a 75 g oral glucose tolerance test (OGTT) extending to 4 hours in 14 patients with idiopathic postprandial s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The first was characterized by lower fasting glucagon and further suppression during OGTT, and the second with fasting hyperglucagonemia and drastic decrease during OGTT. The authors concluded that glucagon suppression in patients with IPS is more substantial than in healthy individuals ( 59 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The first was characterized by lower fasting glucagon and further suppression during OGTT, and the second with fasting hyperglucagonemia and drastic decrease during OGTT. The authors concluded that glucagon suppression in patients with IPS is more substantial than in healthy individuals ( 59 ).…”
Section: Resultsmentioning
confidence: 99%
“…One article investigated both glucagon and AAs (20). In contrast, 12 other articles examined the effect of glucose administration on glucagon (7,(53)(54)(55)(56)(57)(58)(59)(60)(61)(62), and six other articles studied the effect of an OGTT on AAs (63)(64)(65)(66)(67)(68). The articles by Knop (7), Junker (54) and Wang et al (55) were the only trials to include i.v.…”
Section: Characteristics Of Literature Searchmentioning
confidence: 99%
See 2 more Smart Citations